The role of measurements of OP Innovations and Competitiveness (OPIC) for the intelligent growth of Bulgarian economy - Stoyanova, Tsvetana; Sterev, Nikolay (Economics of the 21st Century, 2018)
The Bulgarian Competitiveness Strategy 2020 by the Bulgarian Operational Program Innovations and Competitiveness (OPIC) is closely linked to the smart growth and effective jobs objectives through investments in intellectual property. The national measures, financing projects under the OPIC are create to boost Bulgarian business to be a part of Industry 4.0 as well as to enforce the industrial renaissance. So, the paper aims to discuss the problem of how to measure the results of the implementation of Competitiveness Strategy 2020 and the economic growth in Bulgaria
Ekonomia XXI Wieku = Economics of the 21st Century, 2018, Nr 2 (18), s. 62-70
Keywords: innovations and competitiveness; industrial policy; Bulgarian economy; competitiveness policy measures; innowacyjność i konkurencyjność; polityka przemysłowa; bułgarska gospodarka; środki polityki konkurencyjności